Kajian Penerapan Laboratory Safety Pada Di Lingkungan Universitas Borneo Tarakan - Budi Setiawan; Alfika Henny Barocah (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2025)
The large number of accidents occurring in laboratories is a strong warning for universities to pay more attention to the health and safety of users in laboratories. The University of Borneo Tarakan is one of the universities that has many active laboratories in use. In an effort to minimize work risks that occur in the laboratory, implementation is needed for laboratory safety. The aim of the research is to assess the level of knowledge of students and lecturers at the University of Borneo Tarakan about laboratory safety, and assess the level of implementation laboratory safety in a laboratory at the University of Borneo, Tarakan. This research uses a descriptive method with a quantitative approach. Based on the results of the analysis of the level of knowledge of Borneo Tarakan University students about laboratory safety amounting to 89.26% in the very good category and the level of lecturer knowledge was 89.57% in the very good category. Implementation level laboratory safety in the laboratory at the University of Borneo Tarakan according to students was 58.13% in the medium category and the level of application according to lecturers was 52.43% in the medium category. Meanwhile, the level of implementation laboratory safety in the laboratory at the University of Borneo, Tarakan, according to all respondents, was 61.40% in the good category.